Dose Setting for Dermal Absorption Studies on Dried Foliar Residues. Issue 4 (14th February 2021) - Morgan, Neil; Hewitt, Nicola J; Felkers, Edgars; Wiemann, Christiane; Kluxen, Felix M; Kuster, Christian J
Abstract: Currently, the standard approach to estimate systemic exposure of workers after contact with dried pesticide residues on crops during re-entry activities relies on using the highest identified dermal absorption value for aqueous spray dilutions. However, recent dermal absorption studies with dried residues and their respective in-use dilutions have shown that this is likely to significantly overestimate their dermal penetration potential and, thus, predicted systemic exposure. The choice of appropriate dose levels for these dermal absorption studies has not been defined. Moreover, actual skin loading during re-entry tasks may differ significantly from that achieved by applying a fixed volume of an aqueous dilution, which is the standard practice in generic dermal absorption studies. To address this, we propose an approach to dose setting for dried residue studies within the current European risk assessment framework. Skin loading for studies can be calculated from the existing exposure algorithms and by taking appropriate body surface areas into account. Thus, skin loading in studies will vary depending on the exact nature and duration of the task and the region of the body exposed, reflecting actual exposure scenarios.